What gets a dentist hired? Factors influencing employment of recent dentist graduates in Saudi Arabia - Khalid Talal Aboalshamat; Mohammed Osamah AlHajeeri; Mohammad Abdullah Al Abdullah; Khalid Mohammed Alzahrani; Ammar Abdulmohsen Allehyani (PLoS ONE, 2025)
In Saudi Arabia, the media have highlighted employment struggles among newly graduated dentists. The aim of this study was to assess the factors that influence the employment of dentists who graduated within the last 5 years. This was a cross-sectional study that assessed 241 dentists who recently graduated from dental studies in Saudi Arabia. The assessment was conducted using a validated self-reported questionnaire. Among the participants, 66.39% were employed (20.75% in the governmental sector, 1.66% in academics, 43.98% in the private sector). Employment was associated with being married (p = 0.047), graduated more than a year ago (p < 0.001), and who had sales skills (p = 0.015) in both government and private sectors. Graduates from private universities were associated with employment in the private sector (p = 0.004). Graduates with a higher grade point average (GPA) were associated with employment in government jobs, while lower GPA graduates were associated with private sector employment (p = 0.006). Publishing scientific papers increased employment odds by 53.5% (p = 0.001, R² = 0.071). Applying for government or academic jobs improved odds by 13.4% (p = 0.006, R² = 0.060). Postgraduate applications to the Saudi Commission of Health Specialties (SCHS) raised employment chances by 47.5% (p = 0.002, R² = 0.061). Dentists in government or academic jobs were more satisfied with their salaries (79.61%, p < 0.001) than were private sector employees (26.41%). Dental employment levels in Saudi Arabia are surprisingly better than expected. However, more efforts are needed to improve the employment percentage and increase salary satisfaction in the private sector.